DETERMINANT FACTORS OF LENGTH OF STAY AMONG UNDER-FIVE CHILDREN WITH PNEUMONIA DISEASES: A LITERATURE REVIEW - Casman Casman; Nani Nurhaeni (Alta Dharma Publisher, 2019)
Pneumonia is a public health problem in the worldwide, in Indonesia around 22.7% of under-five child mortality caused by pneumonia. The study aimed at identifying factors associated with length of stay among children under five years with pneumonia. This literature review was conducted in 4 databases: ScienceDirect, EBSCOhost, Clinical Key, and SpringerLink by combining keywords: length of stay; hospitalization; length in hospital; pneumonia; child; pediatric; pediatric; and children. The results showed that the period of length of stay pneumonia ranged 1 to 21 days. Some factors which extend the inpatient period including family history with cigarette smoke, less of nutrient and influenza. Meanwhile, some factors were noted to decrease the length of stay pneumonia among children, including early vaccine, examination, and family empowerment through health education. Mostly factors could reduce or increase LOS pneumonia in children under five years, depending on family factors. It requires further research; it is necessary to consider the effect of family education to decrease LOS pneumonia of children. Keywords: Determination factor, Length of Stay, Pneumonia, Children